Pemanfaatan Sistem Informasi terhadap Efisiensi Operasional Karyawan PT Bina Pertiwi - Rizky Maulana (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to determine the Effect of Information System Implementation on Employee Operational Efficiency. This study uses a quantitative descriptive method, with primary and secondary data sources. Data collection techniques use questionnaire and documentation methods. The population in this study was 100 respondents. The results of this study indicate that the implementation of information systems significantly influences 72% of employee operational efficiency.